Advances in Propulsive Bionic Feet and Their Actuation Principles. (16th July 2014) - Cherelle, Pierre; Mathijssen, Glenn; Wang, Qining; Vanderborght, Bram; Lefeber, Dirk
Abstract : In the past decades, researchers have deeply studied pathological and nonpathological gait to understand the human ankle function during walking. These efforts resulted in the development of new lower limb prosthetic devices aiming at raising the 3C-level (control, comfort, and cosmetics) of amputees. Thanks to the technological advances in engineering and mechatronics, challenges in the field of prosthetics have become an important source of interest for roboticists. Currently, most of the bionic feet are still on a research level but show promising results and a preview of tomorrow's commercial prosthetic devices. In this paper, the authors present the current state-of-the-art and the latest advances in propulsive bionic feet with its actuation principles. The context of this review study is outlined followed by a brief description of the basics in human biomechanics and criteria for new prosthetic designs. A new categorization based on the actuation principle of propulsive ankle-foot prostheses is proposed. Based on simulations, the general principles and benefits of each actuation method are explained. The corresponding latest advances in propulsive bionic feet are presented together with their main characteristics and scientific outcomes. The authors also propose to the reader a comparison analysis of the presented devices with a discussion of the general tendencies in new prosthetic feet.